Esta é a “minha” escola? Representações Sociais de jovens do Ensino Médio sobre o pertencimento à instituição escolar - DINIZ, Marina Murphy (2023)
The present research, developed within the scope of the Graduate Program in Education at the Federal University of Maranhão (PPGE-UFMA), was guided by the following questions: How do students perceive the school and their place within it? Do they feel a sense of belonging to this institution? The objective of the study was to understand the social representations of students from two public high schools in São Luís regarding school belonging. The specific objectives were to discuss the role of the school in identity construction, particularly during adolescence; to identify the relationship between belonging, identity, and student schooling; and finally, to analyze the central categories that give meaning to the student's connection to the school based on the students' own voices. In the development of the study, the role of the school in identity construction was discussed, the relationship between belonging, identity, and schooling was identified, and the central categories that give meaning to the student's connection to the school were analyzed. The theoretical discussion begins with the Theory of Social Representations (MOSCOVICI, 2012, 2015; JODELET, 2008; JOVCHELOVITCH, 1995, OLIVEIRA, 2004; SÁ 1995; GUARESCHI, 1995), then moves on to discuss the relationship between social representations, identity, and belonging (DUVEEN, 1995, 1998; DESCHAMPS; MOLINER, 2009; CIAMPA, 1984; JODELET, 1998), in order to understand the place of belonging in these relationships, and subsequently discusses social representations and the school (ARRUDA, 1998; SÁ; ARRUDA, 2000; SOUSA, 2002; ALVES-MAZZOTTI, 2008). To delineate who the students we listened to are, we drew on theoretical references from Berger; Luckmann (2004), Ariès (1975), Coutinho (2009), Saviani (2019), Freire (2018), and indicated the diversity of youth that exists in Brazil and in the city of São Luís based on national and local research, emphasizing markers that characterize these young people, such as race, class, gender, sexuality, place of residence, and access to technology. To achieve the established objectives, the research was conducted in an exploratory and qualitative manner. The fields of study were delineated based on the collaboration of the subjects involved in daily school life, and the data were obtained through the application of a questionnaire with open and closed questions using the Google Forms platform in the first semester of 2022, with 89 students. From the responses, eleven dimensions of analysis were inferred, organized into: previous representations about the school, meanings of being a student, relationships with others (peers and teachers), meanings attributed to the school, and senses of school belonging. It was possible to infer that the representations of Liceu Maranhense are anchored in the school's historical tradition, while at Centro de Ensino Santa Teresa, they are linked to its territoriality and connection with the people there. The self-evaluation as a student and the evaluation of the relationship with teachers and peers are positive, as demonstrated by the ease of discussing these issues. The meanings of the school point to representations anchored in interpersonal relationships, while belonging itself indicates an objectification linked to hospitality, without forgetting the importance of the pedagogical dimension. Finally, the silences and absences present in the research are also significant, prompting reflections and raising concerns about the need to question the impacts of non-belong